Hubungan Self-Efficacy Matematis dengan Kemampuan Pemahaman Konsep Aljabar pada Siswa SMP - Radhwa Lutfiya Salam; Rostina Sundayana; Tina Sri Sumartini (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Many junior high school pupils still have difficulty grasping algebraic concepts, despite the fact that this is an important foundation for studying mathematics. Students mathematical self-efficacy is one element thought to be connected to this challenge. This study aimed to describe students' mathematical self-efficacy and understanding of algebraic concepts and examine the relationship between these variables. This study used a correlational strategy along with a quantitative approach. 29 junior high school pupils who were chosen using a saturation sampling technique made up the sample. A mathematical self-efficacy questionnaire and an algebraic concept knowledge test were the tools utilized. The data were analyzed using descriptive statistics and the Spearman Rank correlation test. The findings show that while students' mathematical self-efficacy fell into the intermediate group (M = 35.26), their grasp of algebraic concepts fell into the high category (M = 14.83). The correlation coefficient of 0.697 and significance value of 0.001 (p < 0.05) show a positive and significant relationship between the two variables. These results indicate that higher mathematical self-efficacy is associated with better understanding of algebraic concepts, although the correlational design does not permit causal inference.